Transcultural adaptation and psychometric evaluation of the mainland China version of Nursing Home Survey on Patient Safety Culture Questionnaire: a cross-sectional survey based on 50 nursing homes in China - Longhao Zhang; Yaqin Li; Yufei Cheng; Xiuying Hu (BMJ Open)
Objective To provide a validated Chinese-language measurement of the Nursing Home Survey on Patient Safety Culture (NHSOPS) in mainland China. The primary goal is to carry out a transcultural adaptation of the NHSOPS Questionnaire into Chinese and evaluate its psychometric properties.Design A psychometric evaluation study is constructed. First, the ‘translation–back-translation–cultural adaptation’ and the pretesting procedure were followed to introduce the NHSOPS. Second, a cross-sectional survey was used to assess the psychometric properties for the mainland China version of the NHSOPS (M-NHSOPS), and a test–retest survey was then applied.Setting and participants The survey was carried out among 1397 nursing home staff from 50 nursing homes in Southwest China.Outcome measures Exploratory factor analysis (EFA) was used to assess the potential structure, and confirmatory factor analysis (CFA) was then applied. Reliability was assessed by the content validity index, Cronbach’s α and the test–retest value.Results Among the 1397 respondents, 1211 were included (86.7%). EFA was used, and a nine-factor structure was explored. Five factors (Cronbach’s α ＞0.6) were selected into the new structure for the M-NHSOPS. Moreover, data showed that it was suitable for CFA, and convergent validity and discriminant validity were satisfactory. On the other hand, M-NHSOPS contains five dimensions and 22 items. The overall Cronbach’s α value was 0.883; the values of each dimension ranged from 0.648 to 0.913. Additionally, content validity showed significant performance. Eventually, test–retest reliability was 0.892, and each dimension was 0.713, 0.809, 0.924, 0.795 and 0.859, respectively (p<0.001).Conclusions M-NHSOPS has acceptable reliability and satisfactory validity among staff of nursing homes in Southwest China, and further verification among samples in other regions of mainland China is required.